Pneumococcal membrane particles promote serotype-independent cellular and humoral immunity and protect against pneumococcal colonization - Rebecca Dookie; Ana Rita Narciso; Meztlli O. Gaytán; Anandi Narayana Moorthy; Sayoni Chakraborty; Sigrun Thorsdottir; John Boss; Francesco Righetti; Jens Karlsson; Max Heurgren; Staffan Normark; Birgitta Henriques-Normark (Proceedings of the National Academy of Sciences, 2026)
Despite implementation of pneumococcal conjugated vaccines (PCVs) against Streptococcus pneumoniae infections, these diseases are still major contributors to global mortality and morbidity, highlighting the need for a novel immunization strategy. Pneumococci release extracellular vesicles/membrane particles (MP) that are enriched in lipids, virulence factors, and surface proteins, and show great efficacy in protecting against invasive pneumococcal disease in mice. As such, MP present an alternative vaccine strategy. However, an in-depth understanding of how pneumococcal MP interact and modulate the immune system in vivo is currently lacking. In this study, we demonstrate that pneumococcal MP possess robust intrinsic adjuvant properties and conserved antigens, including MalX and PrsA, that support a strong serotype-independent effector and memory Th17 response in mice and humans. Mechanistically, vesicles are sensed through TLR2 and signaling through this receptor is required for the human IL-17 response. Moreover, intranasal immunization with MP expands the tissue resident macrophage populations in the lungs with enhanced functional capacities. Our study also demonstrates that MP immunization in the absence of adjuvant is sufficient to protect against colonization in mice.